Electrical and Photoresponse Properties of Al/p-Si/Y1-xSrxMnO3/Al Heterojunction Photodiodes - Ozmen, Denizhan; Yalcin, Mesut; Yakuphanoğlu, Fahrettin (Springer, 2020)
The electrical and photoresponse properties of Al/p-Si/Y1-xSrxMnO3/Al diodes were investigated by using current-voltage and transient photocurrent measurements. The average ideality factor and barrier height has been calculated as 4.2568 and 0.613 eV respectively. The calculated ideality factor for Al/p-Si/Y1-xSrxMnO3/Al diodes is higher than unity because of the interface states, native oxide layer and series resistance. Also, diodes have exhibited property of photosensitivity. These indicated that the fabrication of diodes can be used optoelectronic device applications.
Keywords: Y1-xSrxMnO3; Photodiode; Ideality factor; Barrier height; Photoresponse